Wawasan Kerukunan melalui Tri Hita Karana dalam Penguatan Pendidikan Karakter Peserta Didik - I Made Sukma Muniksu; Ni Made Muliani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The role of the family is very important in fostering student’s understanding in religious education including religious education with a view of harmony. Because parents and family are the first and foremost education received by students. Not only friends with internal religious students, but students must also be able to make friends with interfaith. Because basically all religions in Indonesia want such harmony. Harmony can be achieved one of them in Hinduism, namely the implementation of Tri Hita Karana. There are five values of the main characters of students to instill insight into religious harmony derived from Pancasila, which is a priority for the development of the PPK (Penguatan Pendidikan Karakter) movement, namely religious, nationalist, integrity, independent and mutual cooperation. Each value does not stand and develop individually, but interact with one another, develops dynamically and forms personal wholeness. Tri Hita Karana's teachings teach students how to carry out their obligations towards God, establish and maintain harmony with others (parents, teachers and friends), and can maintain the natural environment as a sense of devotion to God. To implement Tri Hita Karana, students must be equipped with reinforcement of character education in order to achieve harmony.